(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Now a days Internet is most widely used in all kinds of the information systems. This network is available almost anywhere, anytime, for anyone and can access on many devices like (Computer, Smart-phones, Tablets, Smart-TV, Smart-Watches, Smart-Car many Electronic Devices etc.). People start thinking to connect the Internet to almost all devices for daily use, so they can communicate with each other by taking simple decisions for helping them in their life. Such idea is called the Internet of Things (IOT).The next step is adding the Artificial Intelligence (AI) to Internet of Things (IOT) systems. Artificial Intelligence is increasingly used in daily life. Artificial Intelligence (AI) is an effective science which employs strong enough approaches, methods, and techniques to solve critical real-world based problems. This paper gives overview of Artificial Intelligence (AI), Internet of Things, Techniques used in AI, and it’s Application Areas. This paper also explains the role of AI IOT in Modern-Era E-commerce businesses.